2021
DOI: 10.17843/rpmesp.2021.384.8820
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias en el uso de fármacos para la COVID-19 durante la primera ola de la pandemia en un hospital de Lima, Perú

Abstract: Con el objetivo de evaluar las tendencias en el uso de fármacos en pacientes con la COVID-19 en un hospital del Perú durante la primera ola de la pandemia se realizó un estudio retrospectivo entre abril y septiembre del 2020. Se revisaron las historias clínicas de pacientes hospitalizados por neumonía por COVID-19 en el Hospital Nacional Dos de Mayo (Lima, Perú). De un total de 3103 pacientes, se incluyeron aleatoriamente 381 historias clínicas (77,4% de sexo masculino y una mediana de edad de 44 años). Se obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…A study done in Lima between April and September 2020 revealed that before hospital admission, 44% of patients used some drug, 32% azithromycin, 28.9% ivermectin, and 20.7% corticosteroids. However, the frequency of some used drugs increased over the months [ 20 ]. In addition to the variation in official recommendations, the authors also suggested that drug infodemia could explain this increase [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study done in Lima between April and September 2020 revealed that before hospital admission, 44% of patients used some drug, 32% azithromycin, 28.9% ivermectin, and 20.7% corticosteroids. However, the frequency of some used drugs increased over the months [ 20 ]. In addition to the variation in official recommendations, the authors also suggested that drug infodemia could explain this increase [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of some used drugs increased over the months [ 20 ]. In addition to the variation in official recommendations, the authors also suggested that drug infodemia could explain this increase [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations